Synthesis and Microwave Absorption Properties of Ni0.5Zn0.5Fe2O4/CI Composite Coated with Polyaniline within Paraffin Wax Matrix - Houbi, A.; Zharmenov, A.A.; Atassi, Y.; Bagasharova, Z.T.; Mirzalieva, S.; Karibayev, B.A. (KU Publ., 2022)
Ternary composites of polyaniline/Ni0.5Zn0.5Fe2O4/carbonyl iron (PANI/F/CI) are prepared via two stages. Firstly, Ni0.5Zn0.5Fe2O4 is prepared using a sol-gel method. After that, PANI/F/CI composites are prepared using an in-situ polymerization technique of PANI in the existence of the Ni0.5Zn0.5Fe2O4 and CI. X-ray diffractometry (XRD), Fourier transform infrared (FTIR) spectroscopy, Ultraviolet-visible (UV-vis) spectroscopy, and Thermogravimetric analysis (TGA) are utilized to characterize samples. The morphology of the powders is investigated by Scanning electron microscope (SEM). The electromagnetic interference (EMI) shielding and microwave absorption (MA) properties are measured in the frequency band of 8.8–12 GHz to investigate the microwave characterization. The results refer those microwave absorption properties are related to the absorber thickness and the loading ratio of the absorber within a paraffin matrix. Minimal reflection loss of –30.8 dB at the matching frequency (fm) of 10.3 GHz and the absorption bandwidth under –10 dB (BW–10dB) of 2.8 GHz for 3.4 mm thickness with a surface density (SD) of 3.38 kg/m2 are noticed for the PANI/F/CI composite sample. The maximum shielding efficiency (SE) of 30.12 dB at 11.0 GHz for 3.2 mm thickness is observed for the PANI/F/CI composite sample.
Парафинді балауыз матрицасында полианилинмен қапталған Ni0.5Zn0.5Fe2O4/CI композитінің синтезі және микротолқынды сіңіру қасиеттері
Синтез и микроволновые поглощающие свойства композита Ni0.5Zn0.5Fe2O4/CI, покрытого полианилином в парафиновой матрице
Keywords: polyaniline; carbonyl iron; composites; lightweight microwave absorber; reflection loss; absorption bandwidth; shielding efficiency; matching frequency